Impact of Service Quality on Customer Satisfaction and Customer Loyalty: A Case of Baking Sector of Pakistan - Nawaz, Fatima (Journal of Applied Research and Multidisciplinary Studies, 2022)
Previous decades embraced very high growth in banking sector of Pakistan. Resultantly banking sector indulge in heavy competition among the banking and other financial institutions. Ultimately, the only way to survive and attract customers is the improvement in service quality to attract the customers and fetch the revenue for the concerned bank. The study aims to examine the quality of service being provided by various banks in Pakistan. It was analyzed how customer satisfaction mediates customer loyalty. Four hypothesis were devised to check the various angles of relationship with customer loyalty and service quality. Sample of 200 customers was selected for taking customer satisfaction and customer loyalty. A structured questionnaire was administered to collect the data from bank customers. The analysis through Statistical Package for Social Sciences (SPSS) revealed that there is significant relationship between the customer satisfaction and customer loyalty. The results of study shows that service quality has positive impact on customer loyalty as it is evident in regression I and regression II after inclusion of mediating variable in the model according to Kenny’s approach. So was concluded that service quality indirectly effects loyalty through the mediation of satisfaction.